A qualitative content analysis exploring the portrayal of antibiotic use and antibiotic resistance in UK smallholding print media - Scott, Claire D.A.; Bueno, Irene; Tasker, Alex J.; Buller, Henry; Reyher, Kristen K. (Frontiers in Veterinary Science, 2025)
BackgroundAntibiotic use (ABU) practices and attitudes around antibiotic resistance (ABR) are relatively unstudied for smallholders in the UK. Due to differences in outlook, goals and farming methods, these factors may differ from commercial farmers. To gain insight into how the issues of ABU and ABR are communicated amongst and for smallholders, we completed a qualitative content analysis of smallholding print media.MethodsTo explore how the concepts of ABR and ABU were portrayed, we gathered 129 articles from four UK smallholding magazines published from January 2015 to December 2019; material relating to ABR (from all issues) and ABU (from quarterly issues) was extracted. Guided by framing theory, we identified key themes and sub-themes. We then used qualitative relational content analysis to consider how and when themes and sub-themes appeared together.ResultsIn the theme ‘Antibiotic stewardship’, contributors encouraged practices such as seeking veterinary supervision for ABU or preventing the need for antibiotics for farm animals. In the theme ‘Antibiotics for livestock health’, contributors described the importance of antibiotics to protect animal welfare. ‘Antibiotic stewardship’ occurred alongside ‘Antibiotics for livestock health’ two-thirds of the time, meaning that reference to antibiotic stewardship was common when discussing ABU. Whilst ABU on smallholdings was characterised as infrequent and broadly restricted to singular animals after observation of clinical signs of disease, analysis of reported instances of ABU showed that recommendations described in the theme ‘Antibiotic stewardship’ may not consistently be completed in practice, including seeking veterinary supervision for ABU. In the theme ‘Problems are elsewhere’, contributors ascribed greater significance to groups such as commercial farming or human medicine in their overuse of antibiotics and hence contribution to ABR. Especially where the ‘Problems are elsewhere’ theme occurred alongside ‘Antibiotic stewardship’, contributors appeared to demonstrate a lack of acceptance of responsibility for ABR which ranged from subtle to more overt.ConclusionOur study provides insight into the ways smallholders consider, discuss and use antibiotics in the context of and in relation to ABR. We identify potential facilitators and barriers to antibiotic stewardship on smallholdings and suggest recommendations for how educational material aimed at smallholders could be adapted to better encourage antibiotic stewardship practices.